Pelatihan Pemanfaatan Microsoft Office Dalam Rencana Pembelajaran Bagi Guru SD Negeri 060856 Medan - Yunita Sari Siregar; Rizki Habibi; Jholant Bringg Amelia; Deasy Arisandy Aruan; Jessy Safitri Sitorus (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2023)
At present the use of computers is not only intended for office administration, but can help teachers in the learning process at school. The lesson plan is a learning stage that must be prepared before starting a new semester. In the learning plan there are school teaching materials and modules. To make lesson plans, you can use Microsoft Office, where there are 3 applications, namely Microsoft Word, Microsoft Power Point, and Microsoft Excel. This community service activity was carried out at the 060856 Medan State Elementary School involving 19 teachers and 1 school principal. The results of this activity are expected to increase the use of computer media in the learning process in the classroom and make it easier for teachers to share lesson plans with students in supporting the digitalization era.